ACCI a systems design study - Basiao, Yazmin; Bo-ot, Jose; Ces, Kathy; Luna, Eileen (College of Engineering, 2002)
A systems design study involves looking into a whole system and analyzing this system from the strategic level down to tactical and operational levels. The researchers chose ACCI as the system of study. Being in the country club and golf industry, ACCI is considered an outstanding county club because of its facilities and being strategically located inside a Class "A" residential village. The main objective of the study is to improve the present system at the ACCI. Considering the present system, the researchers documented the organizational structure, the different divisions, the facilities and its capacities, the workforce management, and the environmental aspects of ACCI. After the extensive documentation of the present system, the researchers proceeded to the analysis of the system. The measures of performance of ACCI were then determined to be able to quantify the success of ACCI and know how it is able to compete with the other country clubs. To aid in the analysis on a strategic level, the tools Seven S Analysis, Industry Analysis and SWOT analysis were used. The results of the SWOT analysis were further justified and evaluated through the streamline analysis diagram to determine the core problems of ACCI. Four areas of concern were addressed namely manpower, methods, management and facilities. The last portion of the analysis involved the capacity analysis of the main ballroom and tennis courts. To be able to help ACCI improve and solve the identified problems, the researchers came up with a recommendation which addresses the areas of management, environment, facility and the entire SWOT of ACCI. With these recommendations, a cost-benefit analysis was then performed to determine the probable costs that go with implementing the recommendation and also, on the other hand, the long term benefits it may provide to the company. After which the implementation strategy is shown which includes a Gantt chart for each of the recommendations. This systems study was able to help the researchers know more about the industry involving country clubs. It helped the researchers gain a lot of knowledge on how to analyze from a top management point of view down to the more detailed parts of a service type system.